The relationship between laboratory, Yoyo, and Hoff tests in determining aerobic capacity of players of the national women`s soccer team - Nazarali, P.; Rajabi, H.; Aliabadi, F. (Annals of Applied Sport Science, 2013)
Aerobic capacity bears importance in soccer. Although laboratory tests are of high credibility to measure the oxygen consumption among soccer players in laboratory conditions, field tests simulating the real need of soccer, without requiring complicated equipment, are necessary. The purpose of the present paper is to study the relationship between Hoff tests, Yoyo intermittent recovery test, and laboratory tests in determining the aerobic capacity of players of the national women`s soccer team. Twenty female soccer players have participated in this study. The players executed the laboratory test on treadmill and determining VO2max with the gas analyzer device, Hoff, and Yoyo intermittent recovery test of level two in three separate periods with at least a oneday interval. The aerobic capacity, heart rate, and lactate were measured at the end of every three tests. The lactate level of blood (ICC=0.61) and heart rate (ICC=0.66) had a significant correlation at the end of both laboratory and Hoff tests. The maximal consumed oxygen of Yoyo and laboratory tests didn`t have a significant relationship. As for heart rate and blood lactate, no significant relationship was found at the end of the two tests. Also, no significant correlation was found between the results of Hoff and Yoyo tests, and they can`t be used interchangeably. According to these results, it can be said that Hoff test is a valid test which easily evaluates VO2max, without requiring the equipment imposing a financial burden on the national team, and whose physiological pressure is similar to the laboratory test.